2011
DOI: 10.1186/cc10559
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis induces albuminuria and alterations in the glomerular filtration barrier: a morphofunctional study in the rat

Abstract: IntroductionIncreased vascular permeability represents one of the hallmarks of sepsis. In the kidney, vascular permeability is strictly regulated by the 'glomerular filtration barrier' (GFB), which is comprised of glomerular endothelium, podocytes, their interposed basement membranes and the associated glycocalyx. Although it is likely that the GFB and its glycocalyx are altered during sepsis, no study has specifically addressed this issue. The aim of this study was to evaluate whether albuminuria -- the hallm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 50 publications
(53 reference statements)
3
56
0
1
Order By: Relevance
“…Reactive oxygen species are one of the main culprits in shedding of the glycocalyx, promoting leucocyte adhesion, compromising the endothelial barrier, and causing glomerular filtration dysfunction [38]. During septic renal failure, the glycocalyx is disrupted by the factors described above, leading to albuminuria [39]. In addition to such structures being destroyed in the processes leading to AKI, transmembrane molecules essential for cellular integrity and communication are also compromised.…”
mentioning
confidence: 99%
“…Reactive oxygen species are one of the main culprits in shedding of the glycocalyx, promoting leucocyte adhesion, compromising the endothelial barrier, and causing glomerular filtration dysfunction [38]. During septic renal failure, the glycocalyx is disrupted by the factors described above, leading to albuminuria [39]. In addition to such structures being destroyed in the processes leading to AKI, transmembrane molecules essential for cellular integrity and communication are also compromised.…”
mentioning
confidence: 99%
“…Our research group has recently studied sepsis-associated acute kidney injury (AKI) and, in particular, changes in GBF in an experimental model reliably mimicking human sepsis: the cecal ligation and puncture (CLP) model. Significant alterations in the composition of the GFB anionic components SAs and HA, consisting in decrease and/or structural change associated with loss of GFB permeability-selectivity were revealed (Adembri et al, 2011). Studies performed using different experimental sepsis models have demonstrated various morphofunctional alterations both in the tubules and interstitium, particularly in the cortex (Achparaki et al, 1988;Hurley et al, 1989;Heyman et al, 2002;Aunapuu et al, 2004;Klenzak and Himmelfarb, 2005;Messaris et al, 2008;Heyman et al, 2010;Hsiao et al, 2012), however there are no data regarding the expression of these anionic molecules in the tubulointerstitial compartment.…”
Section: Introductionmentioning
confidence: 97%
“…Sialic acids (SAs) are considered to be among the most important molecules that contribute to the GFB permeable selectivity (Takeda, 2003;Galeano et al, 2007;Quaggin, 2007;Singh et al, 2007;Harvey and Miner, 2008;Adembri et al, 2011). They represent a large family of nine carboxylated sugars (Angata and Varki, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Correcting low blood volume, increasing the effective circulating blood volume in order to ensure effective cardiac output blood flow and organ perfusion are fundamental objective of perioperative fluid therapy (29). Excessive fluid overload is a key factor leading to pulmonary edema and lung injury (30).…”
Section: Eg and Overhydrationmentioning
confidence: 99%